Muslims in India: A demographic and socio-economic profile - Malika B. Mistry (Journal of Muslim Minority Affairs, Vol. 25, No. 3, December 2005, 2005)
This paper presents a demographic and socio-economic profile of the Muslims in India, who form the largest minority in the country. At 120 million strong, Muslims constitute 12 per cent of the population of India. Tracing the origin and ethnicity of Muslims in India, the findings suggest that most Indian Muslims are ethnically Indian since they are the descendents of the early converts to Islam. Many Indians who belonged to the lower castes embraced Islam for its egalitarianism which was practised by the local Sufi saints. The paper provides a demographic history of Indian Muslims, including the growth and distribution of the Muslim population across Indian states over the past century. Comparative fertility and mortality rates are presented for various religious communities to explain the differential growth of the Muslim population. The relative backwardness of the Muslim community, and particularly of Muslim women, is noted as a factor in the comparatively high fertility rates observed among the Muslim population. The paper also reviews the contribution of Muslims to the politics, arts and culture of India, and then goes on to examine the problem of communalism and communal violence that has characterized the Indian political scene. The paper concludes with arguments in favour of ensuring justice and human rights for Muslims, emphasizing the importance of non-governmental organizations (NGOs) and the positive role they could play in enhancing the condition of the Muslim community in India.